Răspuns:
[tex]A =\left[\begin{array}{ccc}1&2&3\\-1&2&0\end{array}\right] =\left[\begin{array}{ccc}-1&1&1\\0&1&0\end{array}\right]+ \left[\begin{array}{ccc}2&1&1\\2&1&0\end{array}\right]+\left[\begin{array}{ccc}0&0&1\\-1&0&0\end{array}\right]\\\\B = \left[\begin{array}{ccc}-2&6\\-1&0\\-4&5\end{array}\right] =\left[\begin{array}{ccc}-1&2\\1&0\\-1&2\end{array}\right]+\left[\begin{array}{ccc}-1&2\\-2&0\\-2&2\end{array}\right]+\left[\begin{array}{ccc}0&2\\0&0\\-1&1\end{array}\right][/tex]
Explicație pas cu pas: